The Effect of Cash Flow and Leverage On Cash Holding In Sharia Banking The Period 2015 - 2020 (Journal of Business and Management, 2022)
Cash is an asset that is very easy to liquidate by the company and can be used as soon as possible to meet the needs of the company's operational activities. Cash holding in the company's storage is cash that will be used for the purposes of the company's operational activities such as to purchase supplies for the company's inventory, to pay off company debts and also for other company activities. In general, there are important factors that will affect the company's cash holding policy, namely cash flow and leverage. Thus, this study aims to determine and analyze the effect of cash flow and leverage on cash holding in Islamic banking. Overall, this study uses 12 listed Islamic banking companies consecutively listed on the Indonesia Stock Exchange for 6 periods from 2015 - 2020. Using panel data regression, this study finds that simultaneously the cash flow variable has a positive effect on cash holding in Islamic banks. However, partially the cash flow variable has a positive effect on cash holding in Islamic banks. In future research, it is possible to conduct research using variables because in this study the cash flow variable, and leverage can only provide an explanation of cash holding with a value of 36.51% so that it is possible to find new ones by using the variable net working capital, investment opportunity and others. In future research, it is possible to use different sub-sectors of companies so that they may get different results in the islamic banking sector.Keywords: Cash Flow, Leverage, Cash Holding, Sharia Banking